Field‐Effect Transistor‐Based Biosensor for pH Sensing and Mapping - Huihui Ren; Kun Liang; Dingwei Li; Yitong Chen; Yingjie Tang; Yan Wang; Fanfan Li; Guolei Liu; Bowen Zhu (Advanced Sensor Research, 2023)
Abstract It is vital to acquire real‐time pH signals with high resolution as pH variation can reflect important information regarding health status and physiological environment. Field‐effect transistor (FET)‐based biosensors (bio‐FETs), a kind of potentiometric sensor, are being rapidly developed for pH detection due to their advantages of high sensitivity, low temperature dependence, and high portability. More importantly, the high scalability of bio‐FETs renders them applicable for achieving high spatial resolution in pH sensing. In this review paper, the design, operation principle, and critical characteristics of the FET‐based pH sensor are introduced. Then, the recent progress in pH mapping with FET sensor arrays, including static array where a sensor pixel is directly addressed by wiring, and active‐matrix array where a sensor pixel is accessed by additional switching FETs, is presented. Last, typical examples of pH sensor arrays in biomedical applications, such as health monitoring and DNA sequencing and elongation are presented.